2010
DOI: 10.1074/jbc.m109.083287
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Huntingtin in Glial Cells Exacerbates Neurological Symptoms of Huntington Disease Mice

Abstract: Huntington disease (HD) is caused by an expansion of the polyglutamine (polyQ) repeat (>37Q) in huntingtin (htt), and age of onset is inversely correlated with the length of the polyQ repeat. Mutant htt with expanded polyQ is ubiquitously expressed in various types of cells, including glia, but causes selective neurodegeneration. Our recent study demonstrated that expression of the N-terminal mutant htt with a large polyQ repeat (160Q) in astrocytes is sufficient to induce neurological symptoms in mice (Bradfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(96 citation statements)
references
References 33 publications
3
93
0
Order By: Relevance
“…30 Impairments in astrocytic function are increasingly recognized as a culprit in neuronal dysfunction in neurodegenerative diseases, 31 such as amyotrophic lateral sclerosis, 32 Rett's syndrome, 33,34 lysosomal disorders, 35 Alzheimer's disease, 36 and HD. 16 Accordingly, astrocyte kir4.1 ion channel deficits contribute to neuronal dysfunction in Figure 4b is the same. See Supplementary Figure 9 for full-length pictures of the blots shown in b, e, and f Figure 4 Genetic modulation of SREBP2 in astrocytes influences neurite outgrowth in HD neurons.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…30 Impairments in astrocytic function are increasingly recognized as a culprit in neuronal dysfunction in neurodegenerative diseases, 31 such as amyotrophic lateral sclerosis, 32 Rett's syndrome, 33,34 lysosomal disorders, 35 Alzheimer's disease, 36 and HD. 16 Accordingly, astrocyte kir4.1 ion channel deficits contribute to neuronal dysfunction in Figure 4b is the same. See Supplementary Figure 9 for full-length pictures of the blots shown in b, e, and f Figure 4 Genetic modulation of SREBP2 in astrocytes influences neurite outgrowth in HD neurons.…”
Section: Discussionmentioning
confidence: 77%
“…11,12 Mutant HTT is expressed in glial cells, 13,14 and transgenic mice overexpressing mutant HTT in astrocytes show age-dependent neurological symptoms. 15,16 Additionally, primary astrocytes overexpressing full-length human mutant HTT show reduced mRNA levels of cholesterol biosynthetic genes, along with impaired cellular production and secretion of apoE. 8 Here we employed molecular and cellular tools to test the impact of cholesterol perturbation between astrocytes and neurons in HD.…”
mentioning
confidence: 99%
“…First, compared with glial cells, lower and impaired neuronal ubiquitin-proteasome system activity, which plays a critical role in clearing misfolded proteins [18] , may account for the preferential accumulation of misfolded Htt in neurons as well as their selective vulnerability [19][20][21] . Second, the expression of mutant huntingtin in glial cells, which could clear excess excitatory neurotransmitters from extracellular space, contributed to neuronal excitotoxicity [2,5,22,23] .…”
Section: Recovery Of Glt-1 Expression and Function By Rapamycinmentioning
confidence: 99%
“…On the membranes of astrocytes, which are the major subtype of glial cells, there are two types of glutamate transporters (GLT-1 and GLAST) that do most of the work in clearing extracellular excitatory neurotransmitters [7,8] . It has been shown that small fragments of N-terminal mutant Htt (such as N-208, N-171), which were reported to be more pathogenic than full-length mutant Htt, caused decreased expression of GLT-1 [2,5] . However, these fragments had been cut occasionally and might not exist in physiological and pathological conditions, so they could not simulate the condition of HD patients completely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation